Algorithms, competition law, public interest - Vese, Donato (P.A. Persona e Amministrazione, 2024)
The growth of artificial intelligence applications and algorithm-based systems has had a profound and far-reaching impact on the market and the economy in general. This has resulted in benefits for consumers, undertakings and the community as a whole. Nevertheless, a considerable number of technological innovations can be employed for the purpose of illicit and anti-competitive practices that may ultimately serve to undermine the public interest. This article presents a taxonomy of the key anti-competitive assumptions based on the application of artificial intelligence and algorithm implementation, demonstrating the major concerns in the legal domain. Accordingly, it recommends the implementation of legal measures to protect both business and consumer interests. These measures should ensure transparency, accountability and responsibility in regard to economic actors employing algorithmic systems and artificial intelligence, with the goal of safeguarding collective and individual interests in a fair and equitable manner.